2005
DOI: 10.1093/treephys/25.5.583
|View full text |Cite
|
Sign up to set email alerts
|

Modeling effects of weather and source-sink relationships on mango fruit growth

Abstract: We modeled the effects of weather and source-sink factors on mango fruit growth. The peach fruit-growth model "Cashoo" was adapted for mango fruit. The model accounts for the main processes of fruit growth, i.e., leaf photosynthesis, fruit demand, fruit respiration, and storage and mobilization of leaf and stem reserves. Simulations for three successive years and for various leaf-to-fruit ratio treatments showed good agreement with observed fruit growth data. Simulations of fruit growth under different climati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
49
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 62 publications
10
49
0
1
Order By: Relevance
“…fruit demand and growth rate. The contribution of temperature to fruit demand can be associated with the daily variation in degree-days used to compute fruit demand in the model of mango growth in dry mass (Léchaudel et al, 2005a). In this study, the model predicted the observed response of fruit growth to changes in temperature between seasons among controlling conditions of carbon and water supplies.…”
Section: Environmental Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…fruit demand and growth rate. The contribution of temperature to fruit demand can be associated with the daily variation in degree-days used to compute fruit demand in the model of mango growth in dry mass (Léchaudel et al, 2005a). In this study, the model predicted the observed response of fruit growth to changes in temperature between seasons among controlling conditions of carbon and water supplies.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Moreover, leaf-to-fruit ratio and the associated changes in carbon availability may have an additional effect on photosynthetic capacity by affecting the relationship between key parameters such as the maximal rate of carboxylation (V cmax ), the light-saturated rate of photosynthetic electron transport (J max ), and N a . Despite the increase in source activity (Urban and Léchaudel, 2005) and the mobilisation of both leaf and stem reserves (Léchaudel et al, 2005a), mango size was smaller in low leaf-to-fruit ratio treatments (Table 2). On the contrary, increasing the leaf-to-fruit ratio from 50 to 100 leaves per fruit increased source size and thus carbon availability, and lead to fruit with higher sugar contents in the flesh.…”
Section: Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These regulations are also considered in the sourcesink models where the conditional net sink strength, and thus the carbon partitioning, is regulated by the history of the sink itself. Moreover, in some source-sink models, the Trees (2008) 22:269-282 273 source strength is regulated by the sink strength (Léchaudel et al 2005) or by the amount of reserves in leaves (Lescourret et al 1998). It is interesting to notice that the high genotypic differences observed in peach photosynthesis by Quilot et al (2002) is not related to the variation of the potential photosynthesis that is very similar between genotypes, but to differences in fruit sink strength.…”
Section: Regulations and Interactionsmentioning
confidence: 99%
“…Pruning intensity also affects the fruit weight under high density planting [7]. Although a high number of fruit bads per plant is desirable to achieve higher yield per unit area, the competition for assimilates among fruits can reduce whole canopy leaf area, which leads to a lower fruit quality [8]. Thus pruning and its intensity is very crucial for proper orchard management and performance of fruit trees.…”
Section: Introductionmentioning
confidence: 99%